Blended learning model of teaching programming in higher education. (30th November 2011) - Mohorovičić, Sanja; Tijan, Edvard
The paper researches the use of ICT in programming courses in higher education (such as learning management systems, web conferencing systems, etc.). Teaching and learning programming has been elaborated and preliminary research has been conducted at the University of Rijeka in which 94 students who attended at least one programming course expressed their experience and opinions regarding e-learning and e-learning systems. A blended learning model is proposed with the aim of improving the quality of teaching and learning programming. Several tools have been researched, which could be useful in preparation and conducting the programming courses.